Description of the first Lessepsian squid migrant, Sepioteuthis lessoniana (CEPHALOPODA: Loliginidae), in the Aegean Sea (Eastern Mediterranean) - LEFKADITOU, E.; CORSINI-FOKA, M.; KONDILATOS, G. (Mediterranean Marine Science, 2009)
Loliginid squids of the Sepioteuthis lessoniana complex are widely spread in the Indo-Pacific Ocean, where they constitute a commercially important resource for neritic fisheries. Sepioteuthis lessoniana is the only Lessepsian squid migrant till now, recorded for the first time in the Mediterranean in 2002 along the Turkish Levantine coasts. Two maturing males, with mantle lengths 193 mm and 244 mm, have been recently caught near the coasts of Rhodes Island (SE Aegean), extending the species distribution northward, into Hellenic waters. Their identity was confirmed by comparison of the main body, beak characteristics and morphometric measurements with those available in the literature for this species. Suspected expansion of the Lessepsian loliginid into the Aegean Sea, due to the gradual warming of the sea, is discussed.